Trichobezoar-Induced Heartburn in a Teenage Girl: A Case Report. (16th May 2018) - Akbar, Shahrazad; Akbar, Lujayn; Akbar, Nuralhuda; Nawras, Ali
One of the most commonly encountered medical problems affecting all age groups in health care is abdominal pain. There are many surgical and medical causes behind this symptom; however, a rare cause of abdominal pain and other unspecific abdominal complaints are gastric bezoars. Gastric bezoars are defined as the accumulation of undigested or partially digested foreign materials in the stomach. They are typically found incidentally during upper endoscopy. Patients may present with abnormal behavior or eating disorders such as pica. Therefore, proper history taking and establishing a good rapport with the patient play a key role in diagnosis. We present a case of trichobezoar-induced heartburn in an 18-year-old female. In this article, we will discuss the types, risk factors, clinical picture, diagnosis, and treatment of this condition.